Oligohydramnios at third trimester and perinatal outcome (Bangladesh Journal of Medical Science, 2012)
Objectives: The purpose of this study to assess the effect of oligohydramnios on perinatal outcome especially at third trimester of pregnancy. Methods: This prospective and observational study was conducted in a private specialized hospital at Dhaka city from January to December 2009. In this study 78 singleton pregnant females with gestational age from 28 - 42 weeks with less amniotic fluid index (AFI) were analyzed for perinatal outcome. Data were expressed as number (percentage). Proportion test was performed for comparison between two groups , P value